Outside options and confidence in Zeuthen-Hicks bargaining - Dias, Luís Miguel Cândido (2019)
The Zeuthen-Hicks bargaining model connects strategic and axiomatic bargaining models by providing a description of the behavior of each party, and showing that the entire process leads to the axiomatically founded Nash bargaining solution. In its original formulation, the model treats parties asymmetrically by considering different decision alternatives of the focal party (who can either accept the opponent’s offer or make a counteroffer, but not quit the negotiation) and the opponent (who can accept the focal party’s offer or quit the negotiation, but not make a counteroffer). We extend the model to consider the full set of possible actions from both sides, which requires explicit modeling of the expectations of the parties concerning outcomes and outside options that become available during the process. We show analytically that under the assumption of concave utilities of both parties, the bargaining process converges to the nonsymmetric Nash bargaining solution. This result provides a new interpretation of the parameters of the nonsymmetric Nash bargaining solution, linking them to behavior in the bargaining process. Furthermore,we perform a simulation study to analyze the outcomes for non-concave utilities.